The Hybrid Approach to Negotiation: Bridging Traditional and Contemporary Practices in 2024 - Daniel Malutan (Journal of Research and Innovation for Sustainable Society)
This article explores the evolution of negotiation practices in 2024, focusing on the integration of traditional and contemporary methods to address the complexities of a rapidly changing global landscape. Traditional negotiations, once defined by formal structures, hierarchical power dynamics, and slow decision-making, are giving way to contemporary approaches that prioritize flexibility, collaboration, and advanced technologies such as Artificial Intelligence (AI) and big data. In response to these shifts, this paper presents a hybrid negotiation model that combines the rigor and structure of traditional techniques with the adaptability and innovation of modern strategies. The hybrid model not only allows negotiators to balance stability with rapid responsiveness but also addresses ethical and sustainability concerns that have become critical in today's global negotiations. By analyzing key factors such as globalization, technological change, and emotional intelligence, this study offers practical insights for negotiators navigating both local and international contexts. This integrated approach ensures more effective and ethical negotiations, fostering long-term partnerships and mutual success.